Optimal investments in private land conservation depend more on landholder preferences than climate change - Brooke A Williams; Carla L Archibald; James Brazill-Boast; Michael J Drielsma; Rajesh Thapa; Jamie Love; Frankie H T Cho; Daniel Lunney; James A Fitzsimons; Md Sayed Iftekhar; Jaramar Villarreal-Rosas; Sarah Bekessy; et al. (Environmental Research Letters)
Effective private land conservation strategies that consider both landholder preferences and future climatic conditions are critical for preserving biodiversity and ecosystem services. Yet, the interaction and relative importance of these factors for conservation planning performance is unknown. Here, we assess the importance of considering landholder preferences and climate change for prioritising locations for conservation tenders to recruit landholders for conservation covenants. To achieve this we develop a planning framework that accounts for the tender process to optimise investment across regions and apply it to koala-focused tenders in New South Wales, Australia, exploring four planning approaches that consider or are ignorant to landholder preferences or climate change. We find that optimal investments depend more on landholder preferences than climate change, and when landholder preferences are ignored, there is little benefit in accounting for climate change. Our analysis reveals new insights into this important interaction.